2021
DOI: 10.1186/s10020-021-00365-5
|View full text |Cite|
|
Sign up to set email alerts
|

METTL14 promotes glomerular endothelial cell injury and diabetic nephropathy via m6A modification of α-klotho

Abstract: Background N6-Methyladenosine (m6A) modification has been implicated in many bioprocesses. However, its functions in diabetic nephropathy (DN) have not been determined. Here, we investigated the role of METTL14, a key component of the m6A methyltransferase complex, in DN. Methods The expression of METTL14 was detected in DN patients and human renal glomerular endothelial cells (HRGECs). In vitro and in vivo experiments were performed to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…Although the role of m 6 A modification and its regulators have attracted much attention, there are only a few papers published on their role in DN. Other studies reported upregulated METTL14 expression in renal biopsy samples from patients with DN and HG-induced glomerular endothelial cells and advanced glycation end product-induced podocytes, and METTL14-dependent m 6 A modification of Sirt1 and α-klotho mRNA contributes to podocyte and glomerular endothelial cell injury, respectively [ 52 , 53 ]. However, the expression of WTAP was increased in DN renal tubules but not glomerulus compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of m 6 A modification and its regulators have attracted much attention, there are only a few papers published on their role in DN. Other studies reported upregulated METTL14 expression in renal biopsy samples from patients with DN and HG-induced glomerular endothelial cells and advanced glycation end product-induced podocytes, and METTL14-dependent m 6 A modification of Sirt1 and α-klotho mRNA contributes to podocyte and glomerular endothelial cell injury, respectively [ 52 , 53 ]. However, the expression of WTAP was increased in DN renal tubules but not glomerulus compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A, METTL3, METTL14, and WTAP were significantly upregulated in the renal cortex of Adriamycin-treated mice than the corresponding controls, and METTL14 was also upregulated in the biopsy samples of patients with DN in comparison to healthy controls ( 34 ). In the high-glucose human renal glomerular endothelial cells (HRGECs), METTL14 was significantly increased compared with the normal-glucose HRGECs, and METTL14 was significantly increased in the kidney tissues of DN patients both at the mRNA and protein levels compared with the normal adjacent tissues of renal carcinoma patients ( 35 ). FTO expression was significantly reduced in the serum samples of DN patients compared with healthy volunteers ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that m 6 A and methylesterase were involved in histopathological changes characteristic of DN. For example, the overexpression of METTL14 in HRGECs markedly increased reactive oxygen species (ROS), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), apoptosis, and suppressed cell proliferation by suppressing the m 6 A modification of α-klotho, while α-klotho can prevent tubular and glomerular injury and delayed DN ( 35 , 48 ). However, another study revealed that podocyte-specific METTL14 deletion upregulated Sirt1 expression, thereby alleviating apoptosis and inflammation, regulating autophagy, and delaying the development of proteinuria and glomerulosclerosis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article (Li et al 2021 ), the authors identified an error in Fig. 2.…”
Section: Correction To: Mol Med (2021) 27:106 101186/s10020-021-00365-5mentioning
confidence: 99%